2011
DOI: 10.1039/c1cp21834d
|View full text |Cite
|
Sign up to set email alerts
|

Water reorientation dynamics in the first hydration shells of F− and I−

Abstract: Molecular dynamics and analytic theory results are presented for the reorientation dynamics of first hydration shell water molecules around fluoride and iodide anions. These ions represent the extremes of the (normal) halide series in terms of their size and conventional structure-making and -breaking categorizations. The simulated reorientation times are consistent with NMR and ultrafast IR experimental results. They are also in good agreement with the theoretical predictions of the analytic Extended Jump Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 59 publications
(111 reference statements)
12
77
2
Order By: Relevance
“…Previous studies 5,7 had suggested that the average jump angle ∆θ varies very little (±5 • ) among the halide series, and for simplicity, we assume a constant ∆θ = 68 • . 5,7 The induced error on the jump contribution to the overall reorientation is expected to be ≈ ±10%, and that on the total reorientation time estimated from the jump model ≈ ±5%. As shown below, the very good agreement between the jump model predictions and the direct calculation of the reorientation times in the simulation suggests that this approximation does not significantly affect our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies 5,7 had suggested that the average jump angle ∆θ varies very little (±5 • ) among the halide series, and for simplicity, we assume a constant ∆θ = 68 • . 5,7 The induced error on the jump contribution to the overall reorientation is expected to be ≈ ±10%, and that on the total reorientation time estimated from the jump model ≈ ±5%. As shown below, the very good agreement between the jump model predictions and the direct calculation of the reorientation times in the simulation suggests that this approximation does not significantly affect our results.…”
Section: Discussionmentioning
confidence: 99%
“…33 While water reorientation is not strictly isotropic, especially in the presence of ions, very little decoupling was observed between the reorientation of various molecular axes next to halide anions. 5 We thus compare the slowdown of the (simulated) OH bond reorientation time and the experimentally-determined value for the HH axis. We stress that this slowdown calculation is averaged over all water OH groups in the solution, and includes water molecules in different environments, ranging from a bulk-like environment to a direct contact with an ion.…”
Section: Simulations With Eccr Forcefieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26 This model was shown to describe successfully the water reorientation dynamics next to a broad range of solutes and interfaces, 26 including hydrophobic 47 and hydrophilic interfaces. 48 Since jumps represent a dominant contribution to the reorientation kinetics (except next to strong H-bond acceptors 49,50 ), differences in the reorientation time usually result directly from changes in the jump time, τ 0 , which is the inverse rate constant for exchanging H-bonding partners. It can be obtained from the side-side correlation function,…”
Section: Hydrogen-bond Jump Picturementioning
confidence: 99%
“…Diffusion of ions is of great interest because of their importance in physical and chemical industry, biology and other areas [1][2][3]. Although many interesting past theories and simulations have focused on structure of solvation shell and dynamics of rigid monatomic alkali cations and halide ions [4][5][6][7][8][9][10][11][12], a large number of chemically and industrially important electrolytes are made of polyatomic ions such as NO 3 -, SO 4 2-etc. that has not received much attention.…”
Section: Introductionmentioning
confidence: 99%